2021
DOI: 10.1186/s12884-021-03889-0
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and vitamin D deficiency risk factors among pregnancy of Shanghai in China

Abstract: Background There is increasing awareness that vitamin D deficiency in pregnant women may be associated with several adverse effects for the mother and newborn. The risks for vitamin D deficiency are unclear. This study was to assess vitamin D nutritional status and vitamin D deficiency risk factors among pregnant women in Shanghai in China. Methods This study is a cross-sectional study conducted in the Sixth Affiliated People’s Hospital of Shanghai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 51 publications
4
18
0
Order By: Relevance
“…More than two-thirds of the 125 enrolled pregnant women presented with VD deficiency or severe VD deficiency. The high prevalence of VD deficiency and insufficiency among pregnant women in this study is similar to those of studies conducted in Switzerland in 2012–2015, China in 2016, Japanese in 2019, and Napel in 2020 [ 30 , 31 , 32 , 33 ]. Swiss women had a mean serum 25(OH)D level of approximately 37 nmol/L (15 ng/mL) and one-third of the overall study population ( n = 1382) had a serum 25(OH)D level < 25 nmol/L (<10 ng/mL); thus, they were seriously vitamin D deficient [ 30 ].…”
Section: Discussionsupporting
confidence: 87%
“…More than two-thirds of the 125 enrolled pregnant women presented with VD deficiency or severe VD deficiency. The high prevalence of VD deficiency and insufficiency among pregnant women in this study is similar to those of studies conducted in Switzerland in 2012–2015, China in 2016, Japanese in 2019, and Napel in 2020 [ 30 , 31 , 32 , 33 ]. Swiss women had a mean serum 25(OH)D level of approximately 37 nmol/L (15 ng/mL) and one-third of the overall study population ( n = 1382) had a serum 25(OH)D level < 25 nmol/L (<10 ng/mL); thus, they were seriously vitamin D deficient [ 30 ].…”
Section: Discussionsupporting
confidence: 87%
“…A high prevalence of vitamin D deficiency up to 62.34% was reported in South China [23] . Recent evidence showed that pregnant women in Shanghai are generally deficient in vitamin D, the result suggest that 72.5% of the participants were vitamin D deficient [24] . At present, the classification standard for the determination of serum 25(OH)D concentration recommended by the IOM is still an indicator commonly used internationally to categorize the vitamin D status in adults.…”
Section: 【 【 【Discussion】 】 】mentioning
confidence: 97%
“…Several researchers have highlighted the growing prevalence of vitamin D deficiency throughout the human population irrespective of age, gender, and ethnicity (A. Gupta, 2014b;Holick, 2007;Jin, 2021;Mendes et al, 2020;Palacios & Gonzalez, 2014;Prentice, 2008;Sizar et al, 2021;Stoffers et al, 2022;C. Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This oil‐soluble vitamin plays multiple roles in human health and well‐being, which have been discussed in detail elsewhere (Gil et al., 2018; Glade, 2013; Hanel & Carlberg, 2020; Hii & Ferrante, 2016; Holick, 2008; Hossein‐nezhad & Holick, 2013; Lappe, 2011; Nair & Maseeh, 2012; Reichrath et al., 2008; H. Wang et al., 2017; White, 2013; Zmijewski, 2019). Several researchers have highlighted the growing prevalence of vitamin D deficiency throughout the human population irrespective of age, gender, and ethnicity (A. Gupta, 2014b; Holick, 2007; Jin, 2021; Mendes et al., 2020; Palacios & Gonzalez, 2014; Prentice, 2008; Sizar et al., 2021; Stoffers et al., 2022; C. Yang et al., 2021). The indispensable role of vitamin D in bone health, calcium–phosphorus homeostasis, and parathyroid homeostasis is well‐reported in the literature (Holick, 2002).…”
Section: Introductionmentioning
confidence: 99%